The metanarrative hall of mirrors reflex action in fiction and film - Stewart, Garrett (New York Bloomsbury Academic, 2022)
"A profound and entertaining new work on contemporary narrative in film and literature from celebrated literary critic, Garrett Stewart"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Fiction -- Technique; Motion pictures -- Philosophy; Narration (Rhetoric) -- Philosophy; Electronic books